2016
DOI: 10.1007/s10461-016-1600-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Human Immunodeficiency Virus/Sexually Transmitted Infection Prevention Interventions Targeting Female Entertainment Workers: A Systematic Review and Meta-analysis

Abstract: Female entertainment workers (FEWs) working in karaoke lounges, bars, pubs, nightclubs, discotheques, dance halls, massage parlours, restaurants (as hostesses or singers) and beer gardens are at high risk for human immunodeficiency virus (HIV)/sexually transmitted infection (STI). The aim of the systematic review and meta-analysis is to evaluate the efficacy of HIV/STI intervention programmes targeting FEWs. Among the 14 included studies, majority were in Asia and targeted native FEWs. Most studies were quasi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Female sex workers (FSWs) are a diverse population operating in different settings such as brothels, streets, online sex forums and entertainment establishments (EEs) [ 1 ]. EEs are karaoke lounges, bars, pubs, nightclubs and discotheques providing entertainment activities such as singing, dancing and social drinking [ 2 ]. Female entertainment workers (FEWs) working in EEs are often indirect sex workers who sell sex in the EEs to supplement their income [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Female sex workers (FSWs) are a diverse population operating in different settings such as brothels, streets, online sex forums and entertainment establishments (EEs) [ 1 ]. EEs are karaoke lounges, bars, pubs, nightclubs and discotheques providing entertainment activities such as singing, dancing and social drinking [ 2 ]. Female entertainment workers (FEWs) working in EEs are often indirect sex workers who sell sex in the EEs to supplement their income [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of HIV/STI was higher among FEWs than brothel-based FSWs in a systematic review [ 9 ]. As FEWs often face difficulties in accessing preventive or healthcare services, they are vulnerable to HIV/STIs [ 2 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participation rate was higher compared with previous intervention studies on FEWs9 due to the use of culturally appropriate recruitment strategies (eg, provision of peer support information for their work) developed from needs assessment along with assistance of peer educators with similar sociocultural background to engage participants during recruitment. Prior to study implementation, the second author (ONYC) also volunteered with NGOs and participated in activities organised for FEWs for nearly a year.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, the outcome effects might not be attributed to the intervention in some of these studies due to limitations in study design. They either lacked multiple pretest and post-test assessments to qualify to be a time-series design or were pretest and post-test designs involving only the intervention group 9. Most of these studies also relied only on self-reported behavioural without biomedical outcome indicators 7–9.…”
Section: Introductionmentioning
confidence: 99%